Education Clusters: The Ukrainian Context - Khmara, M. (Наука та наукознавство, 2015)
The study aims at theoretical and methodological grounding of the role of education clusters in economic development and analysis of their impact on competitiveness enhancement of national education systems, with emphasis on Ukraine. A review of theoretical approaches to interpretati on and definition of the notion “education cluster” is made. Information about entities that may be incorporated in education cluster, objectives and expected results of education clusters is given; their advantages compared with traditional education system and their significance in the regional context are shown. Examples of education clusters and research and education clusters currently operating in Ukraine are given. Метою дослідження є теоретико-методологічне обґрунтування ролі освітніх кластерів у розвитку економіки інноваційного типу, а також їх впливу на підвищення конкурентоспроможності національних систем освіти, зокрема в Україні. Виконано огляд теоретичних підходів до тлумачення та визначення поняття «освітній кластер», наведено інформацію про суб’єкти, які можуть бути учасниками освітнього кластеру, про цілі та очікувані результати діяльності освітніх кластерів, показано їх переваги порівняно з традиційною системою освіти, а також їх значення для розвитку регіонів. Наведено приклади освітніх та науково-освітніх кластерів, що нині діють в Україні. Целью исследования является теоретико-методологическое обоснование роли образовательных кластеров в развитии экономики инновационного типа, а также их влияния на повышение конкурентоспособности национальных систем образования, в частности в Украине. Выполнен обзор теоретических подходов к трактовке и определению понятия «образовательный кластер». Приведена информация о субъектах, которые могут быть участниками образовательного кластера, о целях и ожидаемых результатах деятельности образовательных кластеров, показаны их преимущества в сравнении с традиционной системой образования, а также их значение для развития регионов. Даны примеры образовательных и научно-образовательных кластеров, ныне действующих в Украине.